Comparative analysis of radiofrequency ablation and resection for resectable colorectal liver metastases - Ko, Sanghwa (Baishideng Publishing Group Co., Limited, 2014)
AIM: To evaluate the therapeutic efficacy of radiofrequency ablation (RFA) for resectable colorectal liver metastases (CRLM) compared with that of resection. METHODS: Between June 2004 and June 2009, we retrospectively analyzed 29 patients with resectable CRLMs; 17 patients underwent RFA, and 12 underwent hepatic resection. All of the patients were informed about the treatment modalities and were allowed to choose either of them. RFA including an intraoperative approach was performed by a radiologist; otherwise, hepatic resection was performed by a surgeon. Comparative analysis of the two groups was performed, including comparisons of gender, age, and clinical outcomes, such as primary tumor stage and survival rates. RESULTS: The mean tumor size was significantly larger in the resection group (3.59 cm vs 2.02 cm, P < 0.01), and the 5-year overall survival (OS) rate for all patients was 44.7%. There was no difference in the 5-year OS rates between the RFA and resection groups (37.8% vs 66.7%). Univariate analysis indicated significantly lower 5-year OS rates for patients with a tumor size > 3 cm. The 5-year disease-free survival (DFS) rates were 17.6% and 22.2% in the RFA and resection groups, respectively (P = 0.119). Univariate analysis revealed that in cases of male gender, age > 65 years, T stage < IV, absence of lymphatic metastasis, and tumor size > 3 cm, RFA resulted in significantly inferior 5-year DFS rates compared with surgical resection. CONCLUSION: Surgical resection revealed superior outcomes in the treatment of resectable CRLMs, particularly in cases with a hepatic tumor size > 3 cm.